Comparative study of the diversity and structure of plant-pollinator interactions in forest and agricultural landscapes in Northwestern Morocco - Amine SAMIH; Sergi TRÓCOLI; Latifa ROHI; Hassan FOUGRACH; Mohammed HSAINE; Noureddin MAATOUF (European Journal of Entomology)
Fragmentation and destruction of natural habitats threaten essential plant-pollinator interactions. Despite their importance for biodiversity they remain understudied in the context of ecosystem functioning in Morocco. This study examines the influence of forest and agricultural landscapes in Northwestern Morocco on plant-pollinator interactions by analysing the structure and dynamics of their networks. Data were collected between mid-March and mid-July 2023 at eleven sites in different landscapes. The results show significantly higher richness and abundance of pollinators (Hymenoptera, Diptera and Coleoptera) in the cork oak forest of Larache compared to the Gharb plain. High plant diversity in forest landscapes promotes plant-pollinator interactions, enhancing network stability and resilience and the vulnerability of forest.